THE INFLUENCE OF EMPLOYER BRANDING ON ATTRACTING AND RETAINING HIGH-POTENTIAL EMPLOYEES - Firman Arifianto; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2025)
This study investigates the influence of employer branding on attracting and retaining high-potential employees (HiPos). In the competitive knowledge economy, organizations struggle to secure and keep top talent, with traditional tactics often failing for the high-expectation HiPo cohort. Through qualitative analysis, this research identifies the key employer branding dimensions HiPos value most, revealing a distinct preference for Development and Interest value over generic benefits. The findings demonstrate employer branding's dual role: it functions as an external